2009
DOI: 10.1161/atvbaha.108.176107
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Emissions Induce Vascular MMP-9 Expression and Activity Associated With Endothelin-1–Mediated Pathways

Abstract: Objective Mechanisms of air pollution-induced exacerbation of cardiovascular disease are currently unknown, thus we examined the roles of vascular endothelin-1 (ET-1) and reactive oxygen species (ROS) in regulating mediators of vascular remodeling, namely matrix metalloproteinases (MMPs), following exposure to vehicle engine emissions. Methods and Results ApoE-/- mice were exposed by inhalation to filtered air or gasoline engine exhaust (GEE, 1:12 dilution) 6 h/d for 1 or 7 days. Concurrently, mice were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 31 publications
(41 reference statements)
12
128
1
Order By: Relevance
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31). The present study was designed to determine whether and how PM 10 exposure affected the architecture of existing atherosclerotic plaques and to determine whether the observed ultrastructure was consistent with the characteristics of a more vulnerable atherosclerotic plaque.…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 92%
See 1 more Smart Citation
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31). The present study was designed to determine whether and how PM 10 exposure affected the architecture of existing atherosclerotic plaques and to determine whether the observed ultrastructure was consistent with the characteristics of a more vulnerable atherosclerotic plaque.…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 92%
“…Several studies in the ApoE -/-mouse have shown the transcriptional upregulation of factors associated with vascular remodelling including MMP-3, -7 and -9 following PM 10 exposure (29,30), and MMP-9 following diesel exhaust exposure (31). Future work testing for colocalization of these MMPs with migrating foam cells in the WHHL rabbit model would be of interest.…”
Section: Figure 9) a Protruding Leukocyte Is A Macrophage-derived Foamentioning
confidence: 99%
“…There may also exist some synergy between vapor phase, gas, and particle constituents in relation to instigation of cardiovascular responses. Recently, 364 it was demonstrated in apoE Ϫ/Ϫ mice that whole gasoline engine exhaust over 1 or 7 days increased vascular messenger ribonucleic acid expression of matrix metalloproteinase (MMP)-2 and MMP-9. Levels of ET-1 and ROS were similarly increased.…”
Section: Vascular Dysfunction and Atherosclerosismentioning
confidence: 99%
“…In order to investigate the mechanisms of cardiovascular disease exacerbations induced by traffic-related pollutants, LUND et al [86] examined modulation of vascular MMP-2 and -9 expression and activity by gasoline engine exhaust in a wellcharacterised model of vascular toxicity, the apolipoprotein E knockout (ApoE -/-) mouse. Animals were exposed to gasoline engine exhaust (60 mg?m -3 particulate matter whole exhaust) or filtered air for 6 h?day -1 for a period of 1 or 7 days.…”
Section: Induction Of Mmps By Complex Mixtures (Gases and Particles)mentioning
confidence: 99%
“…1) MMP-2 and -9 can be induced via TLR4 (nickel exposure) [92] or secondary to oxidative signalling (gasoline exposure) [86]. In addition, MMP-9 can be induced via fra-1, a heterodimeric partner of AP-1, which binds to and activates the MMP-9 promoter (DEP exposure).…”
Section: Mechanisms and Consequences Of Mmp Modulation By Air Pollutantsmentioning
confidence: 99%